Global health professions student survey among health professional students from university of Jaipur: A cross-sectional study - Jahanvi Kapadiya; Naganandini Sampath; Kumar Gaurav Chhabra; Pankaj Chaudhary; Sakshi Shukla; Satyendra Singh; Avishek Singh (Wolters Kluwer Medknow Publications, 2024)
Background: Tobacco use among health professionals implies failure on the part of both the beneficiaries and health-care delivery system. This research aimed to assess the knowledge, behavior, and attitude among health professional students. Materials and Methods: A cross-sectional questionnaire-based survey was carried out among health-care students (medical, dental, nursing, physiotherapy, and pharmacy) of NIMS University. The final version of the questionnaire had 43 questions divided into six sections: tobacco use prevalence, secondhand smoke exposure, opinions toward tobacco product prohibition, behavioral/cessation, curriculum/training, and demographics. Data were analyzed using SPSS software. The Chi-square test was applied to find any significant association between smoking and qualitative variables among different health professional students. Results: Five hundred and twenty-five students submitted the response to the online survey. One hundred and five (20%) health-care students were smokers. Pharmacy students had the highest percentage of smokers (50%) and also secondhand smoking exposure (46.87%) was highest among them. Nonsmokers had more favorable attitudes toward banning tobacco products. Medical and dental students were highly trained in tobacco cessation compared to other courses (P < 0.05). Conclusion: In the present study, the prevalence of smoking and exposure to secondhand smoking was high among pharmacy students, whereas knowledge toward tobacco cessation and training for the same was high among medical and dental students. The study concluded that comprehensive tobacco preventive and cessation training among all health professionals should be mandatory to improve their effectiveness in tobacco cessation and as role models also.